Research progress of Traditional Chinese Medicine nursing for patients with diabetes (糖尿病中医护理研究进展) - ZHENG Xiaoyan (郑晓艳); LI Jiayue (李佳玥); ZHANG Ying (张莹); GUO Peng (郭鹏) (中西医结合护理, 2023)
Patients with diabetes will suffer from systemic vascular injury and various complications due to the continuous increase of blood sugar. Diabetes has become a member of the epidemic that seriously threatens human health through concentric cerebrovascular disease, tumors, etc. With the great achievements in the clinical practice of Traditional Chinese Medicine nursing in China, Traditional Chinese Medicine nursing intervention for diabetes is based on the basic theory and practical guidance of Traditional Chinese Medicine, exploring the research of appropriate techniques of Traditional Chinese Medicine nursing to prevent and treat diabetes, and providing better help for the treatment of complications of diabetes patients. This article reviewed the status quo of Traditional Chinese Medicine nursing for diabetic patients in recent years, aiming to play a positive role in improving Traditional Chinese Medicine nursing for diabetic patients and controlling the condition of diabetes. (糖尿病患者会因持续血糖增高导致其全身性血管损伤及各种并发症发生, 是常见的威胁人类健康的流行病之一。糖尿病中医护理干预立足于中医基础理论和实践指导, 探索中医护理适宜技术防治糖尿病的研究, 为糖尿病患者的治疗提供更多方案。本研究就近年来糖尿病患者的中医护理现状进行综述, 旨在为完善糖尿病中医护理及控制糖尿病病情提供参考。)